2003
DOI: 10.3171/foc.2003.14.5.15
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiosurgery for hemangiopericytomas

Abstract: Object Hemangiopericytomas represent a small subset of meningeal tumors. Despite their relatively uncommon nature, they are aggressive tumors known for recurrence. Resection is the standard treatment in most, although regrowth and metastases are common even after resection. The authors evaluate the role of stereotactic radiosurgery in the treatment of recurrent hemangiopericytomas. Methods In a review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 33 publications
2
47
1
3
Order By: Relevance
“…Two groups reported that radiotherapy after an initial resection extended the mean time to local recurrence from 34 to 75 months and extended overall survival from 62 to 92 months. 6,12 Dufour et al 7 reported in their series that HPCs recurred after an average interval of 74 months if they were subjected to irradiation after the first surgical treatment, as compared with an average of 29 months if they were not treated with radiotherapy after initial resection.…”
Section: Multimodal Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Two groups reported that radiotherapy after an initial resection extended the mean time to local recurrence from 34 to 75 months and extended overall survival from 62 to 92 months. 6,12 Dufour et al 7 reported in their series that HPCs recurred after an average interval of 74 months if they were subjected to irradiation after the first surgical treatment, as compared with an average of 29 months if they were not treated with radiotherapy after initial resection.…”
Section: Multimodal Managementmentioning
confidence: 99%
“…24 Even most HPCs treated with GTR and adjuvant SRT tend to locally recur by 6 years after treatment. 6,12 However, cases of local recurrence and distal metastases have been reported more than 20 years out from the initial diagnosis. Therefore, long-term follow-up with annual serial imaging is suggested for optimal management.…”
Section: Multimodal Managementmentioning
confidence: 99%
See 3 more Smart Citations